Project Risks Identification of Steel Construction on Industrial Buildings : A Systematic Literature Review - Syarifah Hidayah (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2021)
Risk is defined as an uncertain event or condition that, if it occurs, can have either a positive or negative effect on the project objectives. This effect can be avoided by using risk management methods, to identify risks, assessing risks either quantitatively or qualitatively, and choosing the appropriate method for handling risks will minimalized the effects. In the study, the scope was to identify the potential risk occurs on steel building work based on the previous research. Using sources based on the previous research, here will be identifying what types of risk factors are most commonly occurs for steel building work. The types of risk that will be discussed here will be divided into three types based on internal risk, external risk, and project risk. Each type of risk includes technical and non-technical risks. Based on the data this study identify that internal risk with technical aspects is the most common type of potential risk occurs on steel structure building work.